Genome‐wide Association Study and Meta‐analysis on Alcohol‐Associated Liver Cirrhosis Identifies Genetic Risk Factors. Issue 5 (29th April 2021) - Schwantes‐An, Tae‐Hwi; Darlay, Rebecca; Mathurin, Philippe; Masson, Steven; Liangpunsakul, Suthat; Mueller, Sebastian; Aithal, Guruprasad P.; Eyer, Florian; Gleeson, Dermot; Thompson, Andrew; Muellhaupt, Beat; Stickel, Felix; et al.
Abstract : Background and Aims: Only a minority of heavy drinkers progress to alcohol‐associated cirrhosis (ALC). The aim of this study was to identify common genetic variants that underlie risk for ALC. Approach and Results: We analyzed data from 1, 128 subjects of European ancestry with ALC and 614 heavy‐drinking subjects without known liver disease from Australia, the United States, the United Kingdom, and three countries in Europe. A genome‐wide association study (GWAS) was performed, adjusting for principal components and clinical covariates (alcohol use, age, sex, body mass index, and diabetes). We validated our GWAS findings using UK Biobank. We then performed a meta‐analysis combining data from our study, the UK Biobank, and a previously published GWAS. Our GWAS found genome‐wide significant risk association of rs738409 in patatin‐like phospholipase domain containing 3 ( PNPLA3 ) (odds ratio [OR] = 2.19 [G allele], P = 4.93 × 10 −17 ) and rs4607179 near HSD17B13 (OR = 0.57 [C allele], P = 1.09 × 10 −10 ) with ALC. Conditional analysis accounting for the PNPLA3 and HSD17B13 loci identified a protective association at rs374702773 in Fas‐associated factor family member 2 ( FAF2 ) (OR = 0.61 [del(T) allele], P = 2.56 × 10 −8 ) for ALC. This association was replicated in the UK Biobank using conditional analysis (OR = 0.79, P = 0.001). Meta‐analysis (without conditioning) confirmed genome‐wide significance for the identified FAF2 locus as well as PNPLA3 and HSD17B13 . Two other previously known loci ( SERPINA1 and SUGP1/TM6SF2 ) were also genome‐wide significant in the meta‐analysis. GeneOntology pathway analysis identified lipid droplets as the target for several identified genes. In conclusion, our GWAS identified a locus at FAF2 associated with reduced risk of ALC among heavy drinkers. Like the PNPLA3 and HSD17B13 gene products, the FAF2 product has been localized to fat droplets in hepatocytes. Conclusions: Our genetic findings implicate lipid droplets in the biological pathway(s) underlying ALC.